BENTUK PENYAJIAN MUSIK GONDANG SABANGUNANBATAK TOBA PADA GRUP MADE NAULI SOUND DI PONTIANAK - Desianti Manullang; Aloysius Mering; Asfar Muniir (Universitas Tanjungpura, 2018)
AbstractThe presentation form in music show is for the harmonic of music show presented to audience. Gondang Sabangunan is a Bataknese music ensemble group composed of 4 type of music instruments which are Taganing, Hasapi, Suling. This research has two problems formulation, which are (a) how music form of Made Nauli Sound music group and (b) how presentation form of Made Nauli Sound music show when performing in shows. Data was gathered with three methods: interview, observation, and documentation. Made Nauli Sound music group base was located in Asrama Gatot Karika V Street, Adisucipto, Pontianak. The respondent of the research was the owner of Made Nauli Sound and drummer of Gondang Sabangunan with interview method. Data analysis was done word by word and the validity check was done using Triangulation. Observation and personnel interview done from April to November 2017. The data analysis result concluded that Gondang Sabangunan (a) music form presents shows in instrumental and combination form. The harmony was formed collectively and performance was done in multiple Batak show especially Christian religion occasions. (b) Music presentation has 3 kind of forms, which are religion, culture, and entertainment purpose. Keywords: Music Presentation Form, Made Nauli Sound Group Music, Gondang Sabangunan.